Faktor-Faktor yang Mempengaruhi Penghindaran Pajak Pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia Tahun 2016-2020 - Fakhrina Marsya Primandita; Dian Nirmala Dewi; Artie Ardhita Rachman (Jurnal Riset Akuntansi, 2024)
This study aims to examine the influence of profitability, firm size, and financial distress on tax avoidance. The population of this study is mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2016-2020. This research utilizes secondary data obtained from the financial statements of mining companies listed on the IDX from 2016 to 2020, which were downloaded from www.idx.co.id. The population of this study consists of 86 mining companies listed on the IDX during 2016-2020. Purposive sampling was employed to select a sample of 102 observations for analysis using multiple linear regression. The findings reveal that firm size and financial distress have a significant impact on tax avoidance, while profitability does not have a significant effect on tax avoidance.